Marine sourced tripeptide SRP and its sustained-release formulation SRP-PLGA-MS exhibiting antihypertensive effect in spontaneously hypertensive rats and HUVECs - Huang, Miaoen; Wang, Tianji; Wang, Yinghao; Deng, Qingyan; Chen, Jinjun; Li, Li; Luo, Hui; Lu, Yingnian (Frontiers in Nutrition, 2024)
Biopeptides from Sipunculus nudus were reported with good ACE inhibitory activity, and the tripeptide SRP was one with the highest ACE inhibition rate. However, the disadvantage of short half-life limited the development of peptide drugs. Moreover, the distinct mechanism of the peptide inhibiting ACE remained unknown. Thus, in this study, a sustained release formulation of SRP-PLGA-MS was designed and prepared. Its long-lasting antihypertensive effect as well as improvement of vascular pathomorphology was verified in spontaneously hypertensive rat(SHR).In addition, the anti-oxidant activity of SRP in human umbilical vein endothelial cells (HUVECs) was evaluated. The results showed that SRP inhibited the production of ROS and NO, which involve the NADPH oxidase, and Keap1/Nrf2 signaling pathway. This study demonstrated that SRP-PLGA-MS had the potential to develop sustained-release drugs for hypertension treatment.